Notas sobre la vegetación de Andalucía. IV. - Pérez Latorre, Andrés V.; Cabezudo, Baltasar (Acta Botanica Malacitana, 2002)
Short notes about Andalusian vegetation. IV. Palabras clave. Vegetación, sintaxonomía, Genistion Izaenselero - polyanthi, Minuartio - Poion ligulatae,Andalucía, España. Key words. Vegetation, syntaxonomy, Genistion haenselero - polyanthii, Minuartio - Po ion ligulatae,Andalusia, Spain.